Usage of sorbents for diminishing the negative impact of substances leaking into the environment in car accidents - Marková, Iveta; Kubás, Jozef; Buganová, Katarína; Ristvej, Jozef (Frontiers in Public Health, 2022)
Background: Car accidents are often accompanied by dangerous substances leaking into the environment. A proper reaction to the leaking substances, utilising appropriate sorbents, is necessary for diminishing the negative impact of such events. Sorbents as substances of initial intervention in car accidents (as well as industrial and ecological accidents) are a crucial tool for solving crises connected with dangerous substances escaping into the environment. The risk resulting from the given realities is described in detail in the introduction of the article. The goal is describing elements of crisis management in dangerous substance leakage and an analysis of sorption resources for quick and efficient interception of leaking substances, water, ethanol, oil, and gasoline in particular, as a reaction to such events. Methods: The quality of a sorption resource is determined by a parameter called the sorption capacity, which has been established according to the ASTM F716-18 standard. Loose nature-based sorbents (peat) and synthetic silicate-based SiO2, Al2O3, Fe2O3 and polypropylene-based ones were observed. The research has been realized on a water, oil, gasoline, and ethanol sorbate. Each experiment was repeated 3 times The results attest to the diversity of sorption capacity in comparing nature-based, silicate-based, and polypropylene-based sorption materials. The highest sorption capacity values were reached with the Sorb 4 sample, which is based on 66% of silica and 18% of alumina. The stated ratio is important, because the Sorb 3 sample contains 85% of silica and 6% of alumina and its absorption capacity values are significantly lower.